Anticoagulation drugs in the perioperative period - Morrison, Ben; Kelliher, Leigh; Jones, Chris (Digestive Medicine Research; Vol 2 (September 2019): Digestive Medicine Research, 2019)
Perioperative consideration of the management of anticoagulation medications is an integral part of any successful enhanced recovery after surgery (ERAS) programme. Patients can present for surgery on one or more of a number of different classes of anticoagulant each of which must be considered on an individual basis to ensure these drugs are withheld, if appropriate, in sufficient time preoperatively and recommenced in a timely manner postoperatively. Many indications for anticoagulation exist and patient suitability for certain classes of drug can be assessed using risk scores such as the CHA2DS2-VASc score for atrial fibrillation patients. Preoperative risk assessment of a patient’s risk of developing a thromboembolism forms a vital part of this management in order to balance the risks of thrombus formation against the risk of bleeding. Venous thromboembolism (VTE) can confer a considerable risk of morbidity and mortality for patients perioperatively but risk can be significantly reduced with appropriate assessment and management of a patient’s risk. The classes of drug discussed in this article are the antiplatelet drugs—aspirin, clopidogrel and dipyridamole; heparins whether unfractionated or low-molecular weight heparin; the heparin alternatives without risk of heparin-induced thrombocytopaenia—fondaparinux and danaparoid; the coumarins, namely warfarin; and direct oral anticoagulants (DOACs). It is important for perioperative physicians to be aware of the method of action and pharmacological effects of these drugs and how these affect their management perioperatively.